2010
DOI: 10.1089/jir.2009.0022
|View full text |Cite
|
Sign up to set email alerts
|

Nitric Oxide Stimulates Interleukin-6 Production in Skeletal Myotubes

Abstract: Strenuous exercise leads to the up-regulation of interleukin-6 (IL-6) production and enhanced nitric oxide (NO) release within the contracting skeletal muscles. In this study, we investigated whether NO regulates IL-6 production in C2C12 myotubes. These cells exhibited a concentration-dependent increase in IL-6 production upon stimulation with NO donors (Z)-1-[N-(2-aminoethyl)-N-(2-ammonioethyl)amino]diazen-1-ium-1,2-diolate (DETA-NONOate), (Z)-1-[N-(3-aminopropyl)-N-(n-propyl)amino]diazen-1-ium-1,2-diolate (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 34 publications
1
18
0
Order By: Relevance
“…However, due to the risk of cytotoxicity, experiments using higher concentration of DETA/NO were not performed. In agreement with our data, NO has been reported to stimulate IL-6 production in murine skeletal myocytes [18] and human blood mononuclear cells [19] by activating ERK1/2 and p38 MAPK-signaling pathways [18]. We also found that ERK1/2 and p38 MAPK signaling were crucial for the DETA/NO-mediated activation of IL-6 in renal epithelial cells.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…However, due to the risk of cytotoxicity, experiments using higher concentration of DETA/NO were not performed. In agreement with our data, NO has been reported to stimulate IL-6 production in murine skeletal myocytes [18] and human blood mononuclear cells [19] by activating ERK1/2 and p38 MAPK-signaling pathways [18]. We also found that ERK1/2 and p38 MAPK signaling were crucial for the DETA/NO-mediated activation of IL-6 in renal epithelial cells.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, two concentrations of DETA/NO were used, and only the highest concentration showed a stimulatory effect on IL-6 production. High concentrations of NO donors may have an inhibitory effect on IL-6 production [18,19], and it is possible that a higher concentration of DETA/NO (> 1 m m ) would have decreased IL-6 also in renal epithelial cells. However, due to the risk of cytotoxicity, experiments using higher concentration of DETA/NO were not performed.…”
Section: Discussionmentioning
confidence: 99%
“…It is also well documented that the development of inflammation is regulated by NO and the compounds that release NO (NO donors) are potent regulatory agents in inflammatory processes (Korhonen et al, ). NO donors have been reported to up‐ and down‐regulate the expression of various inflammatory mediators (Makris et al, ). The activity of NF‐κB can be regulated by various factors including NO and the effects of NO on synthesis of proinflammatory cytokines may be mediated by its action on NF‐κB (Chen et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Muscle is not just a downstream effector of exercise-related circulating factors, it can also be locally stimulated to produce cytokines with contraction (24,49,54,67). In addition, skeletal muscle tissue and cells have been shown to be responsive to stimuli that are not necessarily exercise related, including: endotoxin (17), inflammatory cytokines (16,43,70), catecholamines (17,25,36), low glycogen (33,66), ATP (11), intracellular Ca 2ϩ (2,30), surgical manipulation (60), reactive oxygen species (ROS) (35), and nitric oxide (NO) (44,68). Most of these stimuli occur during conditions of "stress" at either the tissue or the whole organism level.…”
mentioning
confidence: 99%